STAYING DRY OR TAKING THE PLUNGE? FACTORS THAT INFLUENCE PARTICIPATION IN MASTERS’ SWIMMING - Stefan Rosca; Paul Davis; Ian Whyte (The Sky, 2022)
Masters swimming offers training and competition opportunities to adults over the age of 25 years through structured programmes. This study aimed to identify what influenced masters swimmers to engage in training and competition. Semi-structured interviews were used to explore the experiences of 12 masters Swimmers (8 male, 4 females; age range = 23-76 years). Data was recorded, transcribed ‘verbatim’, and thematically analysed. Following analysis, a total of 237 meaning units were identified. They were located into 36 themes before being placed into 8 categories: Achieving Goals, Habituation, Health and Fitness, Organisational Influences, Significant Others, Psychological Benefits, Social, and Swim Specific. The most important findings were themes related to the impact of the coach in their participation, participants’ health and fitness, the positive atmosphere inside the squad /club, competitions (for most), and socialisation. This work has helped to identify a landscape that will assist clubs and organisations to develop and maintain masters swimming programmes. Future research is suggested to broaden the range and numbers of responses geographically and culturally, to consider masters swimming alongside other sporting and non-sporting physical activities in which older people participate and extend the work through theoretical discourse.